READINESS IMPLEMENTATION OF SMART PORT IN INDONESIA - Roni Alfiansyah Ritonga; Nurdin Ahmadi; Tridoyo Kusumastanto; Ruddy Suwandi; Sri Rahardjo Suwito; Sinta Hasriningtyas; Heru Arafat; Agus Soleh (Coastal and Ocean Journal (COJ), 2022)
The logistics system in Indonesia is faced with the problem of high logistics costs, which is 24% of GDP, with a logistic performance index (LPI) in 2018 of 3.15 from a scale of 1-5 (World Bank, 2021). Therefore, the port sector as one of the logistics node points continues to make improvements, one of which is the application of digitization. The process of implementing digitization has begun at each port and nationally with inaportnet, simlala, simpadu and the national logistics ecosystem (NLE), this research was carried out using the perception survey method for all Indonesian Port Expert training participants. The 32nd batch of 2020, with questions referring to the Digital Readiness Index for Ports (DRIP) assessment criteria developed by Connect2SmallPorts. From the results of this study, it was found that the respondents stated that the readiness of port digitization was at a sufficient level with a score of 3.9 from a scale of 1-6. Of the 4 (four) aspects assessed, namely (1) human resource management, (2) the level of usefulness/functionality of information technology (IT) at the port, (3) the level of use of IT at the port and (4) the level of use of IT information resources/ port digitalization, the human resources (HR) aspect has the lowest score of 3.6 which is at a sufficient level. This shows the need for efforts from us together to encourage an increase both in terms of the number and quality of human resources with IT/digitalization capabilities at ports.